The effect of product quality, premium price, and brand image on purchase decisions using sem (Case study Natesh Sanitary Pads) - Goyovi, Julia; Heriyadi, Heriyadi; Listiana, Erna; Juniwati, Juniwati; Mayasari, Endah (Institute of Computer Science (IOCS), 2023)
This research aimed to obtain empirical evidence regarding the influence of Product Quality, Premium Price, and Brand Image on Purchase Decisions. The population in this research was consumers of Natesh Sanitary Pads. There were seven hypotheses put forward for in-depth analysis. The sampling method used a purposive sampling technique with a sample size of 200 respondents. The data collection method was carried out by distributing questionnaires with a Likert scale. The method used for data processing and analysis in this research is the Structural Equation Modeling (SEM) method, which uses the AMOS application. The results of this research showed the relationship or influence of Product Quality, Premium Price, and Brand Image on Purchase Decisions.